2006
DOI: 10.1007/s00417-006-0283-9
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of sampling technique and transport media for the diagnostics of adenoviral eye infections

Abstract: Based on our results, the following recommendations are provided to improve sampling, transport and diagnostic techniques regarding conjunctival swabs for diagnosis of human adenovirus infection: (1) application of local anaesthetics, (2) NaCl-moisturised VTS for shipment of specimens, and (3) detection of HAdV by qPCR. The latter method proved to be superior to virus isolation by cell culture, including subsequent identification by IFA, because it is faster, more sensitive and allows simultaneous handling of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
15
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 19 publications
0
15
0
1
Order By: Relevance
“…Previous studies have shown that factors like taking samples in the late phase of infection and storing samples in improper conditions can decrease the number of positive results (21). Wölfel et al (22) have shown that applying a local anesthetic before sampling was increasing the number of cells from conjunctiva. In the same study, three different transport mediums were compared and it has been shown that the medium containing only sodium chloride gave better results than other two commercial transport mediums in virus isolation and in quantitative PCR (22).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Previous studies have shown that factors like taking samples in the late phase of infection and storing samples in improper conditions can decrease the number of positive results (21). Wölfel et al (22) have shown that applying a local anesthetic before sampling was increasing the number of cells from conjunctiva. In the same study, three different transport mediums were compared and it has been shown that the medium containing only sodium chloride gave better results than other two commercial transport mediums in virus isolation and in quantitative PCR (22).…”
Section: Discussionmentioning
confidence: 99%
“…Wölfel et al (22) have shown that applying a local anesthetic before sampling was increasing the number of cells from conjunctiva. In the same study, three different transport mediums were compared and it has been shown that the medium containing only sodium chloride gave better results than other two commercial transport mediums in virus isolation and in quantitative PCR (22). In this study, conjunctival swab samples were taken from patients suspected of adenoviral conjunctivitis without any anesthetic drug implementation in the acute phase and samples were hold in commercial available viral transport mediums in -70 °C until the day of study.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations